PENGARUH PENGGUNA E-MONEY DI SHOPEE TERHADAP KEPUTUSAN PEMBELIAN YANG SESUAI DENGAN PRINSIP SYARIAH PADA MAHASISWA FEBI UNZAH - Sri Utami; Zahida I'tisoma Billah; Yeni Kartikawati (ITB AAS INDONESIA Surakarta, 2026)
This study aims to determine the influence of e-money usage on Shopee on Sharia-compliant purchasing decisions among students of the Faculty of Economics and Business (FEBI) of Zainul Hasan Genggong Islamic University (UNZAH) in the class of 2022. This study used a quantitative approach with a survey method. The sample size was 103 respondents, determined using a total sampling technique. Data were collected using a Likert-scale questionnaire and analyzed using SPSS, including tests for validity, reliability, normality, simple linear regression, correlation coefficient, and coefficient of determination. The results indicate that e-money usage on Shopee has a positive and significant effect on Sharia-compliant purchasing decisions, with a significance value of 0.000 < 0.05 and a regression coefficient of 0.390. The correlation coefficient (R) of 0.512 indicates a moderate relationship, while the coefficient of determination (R²) of 0.262 indicates that 26.2% of purchasing decisions are influenced by e-money usage on Shopee, with the remainder influenced by other factors. Thus, e-money users contribute to students' purchasing decisions, but still require controls to ensure compliance with Sharia principles.